Hispanic Fathers and Risk for Maltreatment in Father-Involved Families of Young Children - Lee, Shawna J. (2011)
The Hispanic population is the fastest growing segment of U.S. population. However, risks for child maltreatment in the foreign-born and native-born Hispanic populations are largely understudied. To address this knowledge gap, we explore the association of sociodemographic factors, psychosocial parenting factors, and nativity status with Hispanic fathers’ aggression toward their young children (3 to 5 years). Using the Fragile Families and Child Wellbeing Study and the follow-up In-Home Longitudinal Study of Pre-School Aged Children, we examine data for 372 foreign-born (FB; n = 155) and native-born (NB; n = 217) Hispanic biological fathers residing in the home when the study target child was 3 years old. Results of analysis at the bivariate level show FB Hispanic fathers engage in fewer aggressive behaviors than NB Hispanic, White, or Black fathers. Time-lagged path models of Hispanic fathers show FB Hispanic fathers use less aggression than NB Hispanic fathers. Length of time in the United States was not associated with parenting aggression. Path models also examine paternal psychosocial factors such as alcohol use, depression, parenting stress, and involvement in caregiving, and control for the child’s aggressive behavior. Results suggest one reason Hispanic children do not face heightened risk for child welfare involvement, despite socioeconomic risks, is that FB Hispanic fathers use less aggression toward their young children. An implication of this finding is that socioeconomic and parenting behavior risks must be considered separately when practitioners are considering issues related to the representation of minority children in the child welfare system.